Contact Simulation and Dynamic Performance Test of Ease-off Modified High Reduction Hypoid Gears - Gu Dewan; Wei Bingyang; Ren Minghui; He Hongtu (Jixie chuandong)
Aiming at the problems of insufficient curvature of the tooth profile of the wheel of the high reduction hypoid (HRH) gear, and high twist of the tooth surface of the pinion with a large helix angle, a method of using a tool to modify the wheel to realize the point contact of the tooth surface is proposed; the pinion adopts the general hobbing method, which simplifies the machining parameters of the machine tool. Three-dimensional models of wheels and pinions and Ease-off topological surfaces are established; the contact performance parameters of tooth surfaces, such as the contact path, differential curvatures, transmission error, etc. are analyzed. The contact areas of the tooth surface before and after modification are compared by 3D motion simulation，and the edge contact is avoided after modification, and the contact area is located in the middle of the tooth surface near the small end, which is consistent with the actual contact spot of the gear. The dynamic performance test of HRH gear reducers has been completed, the gear meshing transmission performance is excellent, and the meshing quality is stable, which verifies the reasonable control of the designed HRH gear modification amount, and the correct theoretical calculation and motion simulation.